Language and community-based tourism use, needs, dependency, and limitations - Nomnian, S.; Trupp, Alexander *; Niyomthong, W.; Tangcharoensathaporn, P.; Charoenkongka, A. (Society for South-East Asian Studies, 2020)
Language and tourism are essentially interconnected by the cross-border movement of tourists and the resulting encounters of people who often speak different languages. These relationships, however, have not been explored very much in the context of community- based tourism (CBT), a kind of tourism that has the potential to enhance communities’ socioeconomic growth, language skills, and cultural heritage. This study explores local communities’ perceived English language needs and challenges for tourism purposes in Thailand’s second-tier provinces of Chiang Rai and Buriram. Informed by fieldwork observations, semi-structured, and focus-group interviews, the findings reveal four key issues: i) the limitations of host-guest interaction and communication, ii) dependency on tour guides, iii) communities’ current communicative English needs, and iv) language users’ sociocultural and linguistic identities. In the cross-cultural tourism encounter, English was needed by the communities despite its limited use by CBT leaders and mem- bers. Cultural identities of the communities and individual speakers were constructed by tour guides whose interpretations of cultural meanings could have been lost in trans- lation. Despite the hegemonic lingua franca status of English, multilingual competence among CBT professionals should be promoted to facilitate community communication and more independence from external translators and cultural brokers. Driven by Thai- land’s current economic development model, information and communication technol- ogy (ICT) could be used to help meet Sustainable Development Goals (SDGs) 4 (Quality Education) and 8 (Decent Work and Economic Growth) by promoting lifelong learning opportunities and socioeconomic development for remote tourism destinations.